Note, à propos des noms vernaculaires chinois dans la Flora cochinchinensis (1790) de Loureiro - André-Georges Haudricourt; Georges Métailié (Revue d'ethnoécologie)
Botanist Edmer D. Merrill noted that vernacular plant names in some ancient botanical texts can help botanists identify the original plants. In the same paper, he noted that they could also be misleading. On the basis of this apparent contradiction, we have considered the Chinese plant names chosen by Loureiro in his Flora cochinchinensis (1791), and, comparing them to the names found in modern Chinese books, we have found that the two assertions are true; however, the first one reflects rather frequent cases contrary to the second one.